Effective Coastal Climate Services—An End-User Perspective for Resilient Infrastructure - Simm, Jonathan; Gouldby, Ben; Lumbroso, Darren; Matthewson, Tom (Frontiers in Marine Science, 2021)
This paper focusses on identifying the responses to coastal climate change that are of interest for decision-making by end users and the delivery and the necessary communication process for this information. The focus is on representation of climate (response) information in a form that provides sufficient clarity in the midst of uncertainty for end-users who are seeking to develop or maintain resilient infrastructure. The paper recommends that the use of the term climate services in situations unrelated to supporting adaptation to and mitigation of climate change should be avoided. Better investment decisions could be made if Bayesian frameworks were used to assign probabilities to RCP scenarios. Associated predictions need to cover all types of climate change influences not just sea level rise and ideally provide concurrent time series to allow evaluation of dependencies. Guidance on climate information published by official bodies needs to adopt a consistent approach, with a clear narrative that describes the transition from science to guidance. The form in which climate services information is needed for the required end user decisions needs careful thought, including appropriate communication of the associated uncertainties using good practices and experiences from related sectors.